Low temperature charge transport in arrays of single-walled carbon nanotube bundles with radiation-induced defects - Vainberg, V.V.; Poroshin, V.N.; Pylypchuk, O.S.; Tripachko, N.A.; Yaskovets, I.I. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2019)
Electric transport properties and magnetoresistance (MR) of the array of metallic single-wall carbon nanotube bundles irradiated by the electron flux with the energy close to 1 MeV or Co⁶⁰ gamma quanta have been investigated within the temperature range T = 1.8…200 K and in the magnetic fields up to 5 T. The power-law behavior of the conduction vs temperature was observed within the range 50 to 200 K, which is typical for conduction of quasi-one-dimensional systems in the model of the electron gas as the Luttinger liquid. The change in power exponent α with the radiation dose and its deviation as compared to α for the non-irradiated samples is related to changing the number of conduction channels in the bundles as a consequence of the radiation defects appearing. At temperatures below 50 K, the Mott three-dimensional hopping conduction is realized. Using the measured dependence of conduction on the temperature and electric field, the density of electron states in the vicinity of the Fermi level, which participate in the hopping charge transport, and the localization length of charge carriers in these states have been determined. These parameters determining the hopping mechanism of the charge transport are noted to depend on the radiation dose. The magnetoresistance in the Mott-type hopping conduction region was negative in the whole range of magnetic fields, while at the large fields an upturn to the positive change was observed. The mechanisms of the negative and positive MR components are discussed.